Osteoporosis awareness among Indian women - Ayesha, .; Sharma, Rina; Khan, Yasir Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Osteoporosis is a major public health problem globally. Despite being a common problem, majority of the women are unaware of it. Awareness varies widely according to the level of education. In present study we have tried to assess the awareness of female patients attending the hospital. Methods: 100 female patients attending gynae OPD were asked to fill a simple questionnaire after taking informed consent. Age, parity, address, and level of education were noted. Data was analysed statistically by SPSS and level of significance was calculated by Chi square test. Results: Majority of these women belonged to rural background (85%) and around 64% of the women were educated (primary schooling and beyond). About 46% of the women had some awareness regarding osteoporosis and its prevention. Majority (54%) were unaware. Level of awareness varied significantly with level of education (p=0.006). Urban dwellers were more aware about osteoporosis when compared to rural women (p=0.004). Conclusions: Overall awareness about osteoporosis is low and here is a need to have community based awareness campaigns regarding osteoporosis. Educational programmes need to target on women coming from rural background and those with low education.